En kvantitativ modell för Cdc42 under påverkan av ROS i polariseringsfasen hos S.Cerevisiae - Björk, Anton; Larsson, Julia; Svedberg, Patrik; Limeta, Angelo (My University, 2017)
Can a reduction of oxygen radicals prolong life? In this bachelor thesis, the impact of reactive oxygen species, abbreviated ROS, on the protein Cdc42 is studied using mathematical modelling. Cdc42 is active during polarization in yeast cells, which creates asymmetry in the cell before division. Research indicates that ROS is a contributing factor to ageing and can damage both DNA and proteins. It has also been shown that the polarization process is less efficient in older cells. Cdc42 is a protein in yeast with homology in humans. Conclusions from experiments in yeast can therefore shed light on similar mechanisms in humans. Three models of increasing complexity, consisting of systems of differetial equations, for Cdc42 under the impact of ROS were developed. Existing experimental data have been used in parameter estimation. Among other relevant parameters, the levels of damaged Cdc42 were estimated. To get a deeper insight regarding parameter estimation, an in-house routine has been created using MATLAB. The parameters have also been estimated in the systems biology software Copasi. The results show that at least two of the three models are able to simulate the concentration distribution of Cdc42 during polarisation and that ROS has a negligible impact on Cdc42 during this period of time. The in-house routine in MATLAB can perform parameter estimations on models with few parameters but gives misleading results when applied to models with many parameters. The conclusion that ROS has little impact on Cdc42 does not come as a surprise. However, there is a lot in the developed models that can be improved to make them more reliable. A thorough investigation of the identifiability of the model parameters is needed if the ODE systems should be further developed. The reason that the in-house program is unable to estimate the parameters of the more complicated models is lack of programming time. With a few modifications, the program should be able to perform more complicated parameter estimations.
Keywords: Grundläggande vetenskaper; Matematik; Basic Sciences; Mathematics